Predicting sustained ventricular arrhythmias in dilated cardiomyopathy: a meta‐analysis and systematic review. (14th April 2020) - Sammani, Arjan; Kayvanpour, Elham; Bosman, Laurens P.; Sedaghat‐Hamedani, Farbod; Proctor, Tanja; Gi, Weng‐Tein; Broezel, Alicia; Jensen, Katrin; Katus, Hugo A.; te Riele, Anneline S.J.M.; Meder, Benjamin; Asselbergs, Folkert W.
Abstract: Aims: Patients with non‐ischaemic dilated cardiomyopathy (DCM) are at increased risk of sudden cardiac death. Identification of patients that may benefit from implantable cardioverter‐defibrillator implantation remains challenging. In this study, we aimed to determine predictors of sustained ventricular arrhythmias in patients with DCM. Methods and results: We searched MEDLINE/Embase for studies describing predictors of sustained ventricular arrhythmias in patients with DCM. Quality and bias were assessed using the Quality in Prognostic Studies tool, articles with high risk of bias in ≥2 areas were excluded. Unadjusted hazard ratios (HRs) of uniformly defined predictors were pooled, while all other predictors were evaluated in a systematic review. We included 55 studies (11 451 patients and 3.7 ± 2.3 years follow‐up). Crude annual event rate was 4.5%. Younger age [HR 0.82; 95% CI (0.74–1.00)], hypertension [HR 1.95; 95% CI (1.26–3.00)], prior sustained ventricular arrhythmia [HR 4.15; 95% CI (1.32–13.02)], left ventricular ejection fraction on ultrasound [HR 1.45; 95% CI (1.19–1.78)], left ventricular dilatation (HR 1.10), and presence of late gadolinium enhancement [HR 5.55; 95% CI (4.02–7.67)] were associated with arrhythmic outcome in pooled analyses. Prior non‐sustained ventricular arrhythmia and several genotypes [mutations in Phospholamban ( PLN ), Lamin A/C ( LMNA ), and Filamin‐C ( FLNC )] were associated with arrhythmic outcome in non‐pooled analyses. Quality of evidence was moderate, and heterogeneity among studies was moderate to high. Conclusions: In patients with DCM, the annual event rate of sustained ventricular arrhythmias is approximately 4.5%. This risk is considerably higher in younger patients with hypertension, prior (non‐)sustained ventricular arrhythmia, decreased left ventricular ejection fraction, left ventricular dilatation, late gadolinium enhancement, and genetic mutations ( PLN, LMNA, and FLNC ). These results may help determine appropriate candidates for implantable cardioverter‐defibrillator implantation.